The impact of changes in scale configuration on the gangsa instrument of the Bhavana Ethnic Mataram as an Indonesian music innovation - Gde Agus Mega Saputra; Galih Suryadmaja; Dewi Puspita Ningsih (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
The use of traditional instruments in Bhavana Ethnic's musical compositions is one of the innovative aspects of Indonesian music offered. This Indonesian authenticity emerges through the characteristic sounds and drumming patterns that are presented in composing the harmony of the musical works. The innovation in question is the group's efforts to change the composition and configuration of the notes and scales on the gangsa  instrument. An instrument adopted from the Balinese gamelan ensemble. Making adjustments to the reality of traditional music in the creative process. The aim of this research is to explain the importance of innovation in the creative (music) process. Seeing how the Bhavana Ethnic group's perspective understands the reality of tradition in gangsa  instruments, the idea emerged to change the composition and configuration of the notes in an effort to meet the aesthetic needs in the work. This research was conducted using qualitative methods. Researchers as the main instrument to understand the impact of changes in the tone composition and scale configuration of bronze instruments in natural conditions. The research results are that changes in aspects of the instrument's pitch configuration have implications for changes in the number of tones, pitch range, rules, melodic pattern system, and instrument function in the ensemble. The result of the musical innovation process carried out is that there is a tendency for interval patterns in the selection of tones in each musical creation process. The tendencies for interval patterns in question include the 2- ½ -1- 2 -½ pattern on the major scale, and 1-1- 1½ -1 -1½ on the minor scale.